2010
DOI: 10.1007/s11738-010-0522-x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of malate dehydrogenase in transgenic tobacco leaves: enhanced malate synthesis and augmented Al-resistance

Abstract: Numerous studies with transgenic plants have demonstrated that overexpression of enzymes related to organic acid metabolism under the control of CaMV 35S promoter increased organic acid exudation and Al-resistance. The synthesis of organic acids requires a large carbon skeleton supply from leaf photosynthesis. Thus, we produced transgenic tobacco overexpressing cytosolic malate dehydrogenase (MDH) cDNA from Arabidopsis thaliana (amdh) and the MDH gene from Escherichia coli (emdh), respectively, under the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 44 publications
4
38
0
1
Order By: Relevance
“…5). Consistent with this, it has been demonstrated that malate synthesis has been increased through overexpression of cytoplasm-localized MDH in alfalfa (Medicago sativa) and tobacco (Nicotiana tabacum; Tesfaye et al, 2001;Wang et al, 2010). We found that SgMDH1 was also localized in the cytoplasm through the transient expression of SgMDH1 in Arabidopsis mesophyll protoplasts (Supplemental Fig.…”
Section: Sgmdh1 Plays Critical Roles In Mn Tolerance Of Fine-stem Thrsupporting
confidence: 86%
“…5). Consistent with this, it has been demonstrated that malate synthesis has been increased through overexpression of cytoplasm-localized MDH in alfalfa (Medicago sativa) and tobacco (Nicotiana tabacum; Tesfaye et al, 2001;Wang et al, 2010). We found that SgMDH1 was also localized in the cytoplasm through the transient expression of SgMDH1 in Arabidopsis mesophyll protoplasts (Supplemental Fig.…”
Section: Sgmdh1 Plays Critical Roles In Mn Tolerance Of Fine-stem Thrsupporting
confidence: 86%
“…Increasing organic acid exudation has been tested as a possible means to enhance Al tolerance; for example, through increasing the activities of the following enzymes: (i) citrate synthase (Barone et al 2008;Deng et al 2009;Han et al 2009); (ii) malate dehydrogenase (Tesfaye et al 2001;Wang et al 2010); (iii) malic enzyme (Sun et al 2014); (iv) pyruvate tolerance genes (such as Al-activated malate transporter 1 (AtALMT1) and multidrug and toxic compound extrusion 1 (AtMATE1)) could improve Al 3ĂŸ exclusion by associating with the exudation of organic acid (i.e., citrate, malate, or oxalate). In addition, ALS1 is implicated in Al 3ĂŸ sequestration in the vacuole after chelation of Al 3ĂŸ with OA in the cytosol.…”
Section: Role Of the Tca Cycle In Root Developmentmentioning
confidence: 99%
“…Modulation of OA metabolism enhanced Al tolerance and secretion of citrate and/or malate in transgenic tobacco and papaya ( Carica papaya ) plants overexpressing a Pseudomonas aeruginosa CS [108], rape plants [58], and carrot ( Daucus carota ) cells [109] overexpressing a mitochondrial CS ( mCS ) from A. thaliana , Nicotiana benthamiana plants overexpressing an mCS from C. junos [24], tobacco plants overexpressing a cytosolic MDH from A. thaliana , an MDH from Escherichia coli [110] and a CS from rice mitochondria [111], alfalfa ( Medicago sativa ) plants overexpressing a alfalfa nodule-enhanced form of MDH ( neMDH ) [112], and tobacco plants overexpressing pyruvate phosphate dikinase ( PPDK , EC 2.7.9.1) gene from Mesembryanthemum crystallinum [113]. However, Delhaize et al showed that the expression of a P. aeruginosa CS in tobacco did not result in enhanced citrate accumulation or secretion, despite generating transgenic tobacco lines that expressed the CS protein at up to a 100-fold greater level than the previously described CSb lines [40, 108].…”
Section: Aluminium-induced Secretion Of Organic Acid Anions From Rmentioning
confidence: 99%
“…Overexpression of mitochondrial CS also resulted in increased citrate secretion and enhanced Al tolerance in A. thaliana [134], rape [58], N. benthamiana [24], and tobacco [111]. In tobacco, overexpression of cytosolic MDH genes from A. thaliana and from E. coli led to increased malate secretion and enhanced Al tolerance [110]. Zhang et al reported that overexpression of a C. junos MDH in tobacco conferred Al tolerance [135].…”
Section: Genetic Engineering Technology For the Secretion And Biosmentioning
confidence: 99%